Designing and Offering a Customer Trust Model in the Marketing Ecosystem Based on Blockchain Technology - Ghavidast Kouhpayeh, Mahbubeh; Doshman Ziari, Esfandiar; Rousta, Alireza (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: The main purpose of the current research is to designing and presenting a model for building customer trust in the marketing ecosystem based on blockchain technology and based on the identification and introduction of trust-building elements and functions arising from blockchain technology in marketing actions.Methodology: In this study, by adopting a qualitative approach, the researcher seeks to identify the antecedents and consequences of building customer trust in the marketing ecosystem based on blockchain technology. In this regard, the required data were collected based on the opinions of experts in the field of digital marketing and advanced information technology and semi-structured interview tools and were analyzed based on thematic analysis method and the use of MaxQDA software.Findings: The analysis of the collected data in the research resulted in the extraction of 64 main themes with a frequency of 264 codes which after the final categories, these themes provided seven general antecedents and two general consequences of applying blockchain technology in order to build trust among customers of a marketing ecosystem.Conclusion: Therefore, in this context, it is possible to design a mechanism to paying commissions to agents and brokers in case of implementing this technology.